Kazakhtanu as intersubject basis and complex justification of natural, spiritual revival (Journal of Philosophy Culture and Political Science, 2018)
Kazakhtanu as a new system of philosophical and humanitarian knowledge penetrates into the depth of culture, life traditions of the Kazakh people; it composes the political and socio-humanitarian base of Kazakhstan; corrects the search of trend and the scale of implementation of the principles of spiritual modernization in the public consent and scientific-cultural cooperation. Also it develops the models of the spiritual rapprochement of people of the republic and cultural – humanitarian contacts in international context.Kazakhtanu presents a new educational discipline, a complex technique of fixing of an integral image and purposeful development of national consciousness in the national state, methodology of experience of development of the Kazakhstan society. The subject area, functional mission, purpose and tasks, stages and standards of studying of new discipline from the point of view of cultural science and ethno-pedagogical education are specified, ordered by the author and offers its understanding of the essence of problems to readers.Key words: Cultural and humanitarian development, spiritual revival, national identity, national value, social and spiritual modernization.